STRATEGI PEMASARAN PRODUK BANK SYARIAH DALAM PERSAINGAN BISNIS PERBANKAN NASIONAL - Irfan Harmoko (WADIAH, 2017)
The sharia banks are the financial institutions that operate on the principles of sharia or Islamic law which acts as an intermediary institutions. The growth of sharia bank in Indonesia is quite good, but the market share is still lacking. Some efforts would be solve this problem, as one of them is increasing the market share that gradually increase new costumers. It can be done by creating marketing strategy among others making a sharia banking product that is easily understood by the public, cooperating with the conventional bank to make a sharia service office (KLS), or make a financial service mobile. Keywords : sharia banking product, marketing strategy.